Les ressorts de la fidélité des pratiquants dans une fédération sportive - Claude Lafabrègue (Temporalités)
This is a study of the social conditions likely to encourage the loyalty of practitioners towards their sports federation. Taking note of the increasing sporting rationalization in many national federations, the research resorts to an explanatory model combining two temporal forms of causality. One, structural, stipulates that loyalty comes from within, starting from the organisational devices set up by the federal institution ; the other, processual, considers that it occurs in the course of the career. The articulation of these two axes of analysis is used to examine hoz the loyalty of practitioners is indebted to the events affecting the proper sporting value granted to them by the federal institution.